Glasdegib plus low-dose cytarabine for acute myeloid leukemia: Practical considerations from advanced practitioners and pharmacists. (April 2021) - Relias, Valerie; McBride, Ali; Newman, Matthew J; Paul, Shilpa; Saneeymehri, Seyyedeh; Stanislaus, Genique; Tobin, Jennifer; Hoang, Caroline J; Ryan, Joanne C; Galinsky, Ilene
Objective: Acute myeloid leukemia (AML) is primarily a disease of older adults. These patients may not be candidates for intensive treatment, and there has been an ongoing need for treatment options for this group. We review the use of glasdegib, a hedgehog-pathway inhibitor available for use in combination with low-dose cytarabine (LDAC). Data Sources: PubMed and relevant congress abstracts were searched using the term "glasdegib". In addition, based on our experience with glasdegib, we considered treatment aspects of particular relevance to pharmacists and advanced practitioners. Data Summary: In a randomized phase II study, the combination of glasdegib plus LDAC demonstrated superior overall survival versus LDAC alone (hazard ratio 0.51, 80% confidence interval 0.39–0.67, p  = 0.0004). The trial reported adverse events (AEs) of special relevance for older patients, such as hematologic events, gastrointestinal toxicity, and fatigue, as well as AEs associated with Hh-pathway inhibitors (alopecia, muscle spasms, dysgeusia). Educating patients about typical AEs can facilitate adherence as well as early AE identification and proactive management. For LDAC, which is a long-established therapy in AML, various stages of delivery need consideration, with attention to individual circumstances. Practical measures such as dispensing a longer supply can reduce the number of return clinic visits, providing a meaningful difference for many patients. Conclusions: Pharmacists and advanced practitioners play important roles in treatment with glasdegib plus LDAC. Ultimately, framing plans for treatment delivery within the individual circumstances of each patient may enable them to stay on therapy longer, giving them the greatest potential to achieve benefit.